Authentic Assessment Berbasis Merdeka Belajar dalam Pembelajaran Sastra Berketerampilan Pikir Taraf Tinggi (HOTS) untuk Mencegah Learning Loss di Sekolah Menengah - Neina, Qurrota Ayu; Qomariyah, U'um; Aditia, Restu (Universitas Negeri Semarang, 2022)
The purpose of this research is to present a needs analysis and the principles of developing an authentic assessment instrument based on the principal of freedom to learn (merdeka belajar) in higher order thinking skills (HOTS) literature learning to prevent learning loss in secondary schools. This research uses the Borg and Gall R and D procedures method. It is adjusted to the actual research objectives and conditions. This research will focus on the first and second steps, there are (a) research and information collecting and (b) planning. The initial study includes the needs analysis which includes an analysis statement from the teachers and students in developing an authentic assessment instrument. Based on this initial study, there were formulated to be some principle: objectives, organization, types of tests, and final assessments.